Role of endoplasmic reticulum Ca2+ signaling in the pathogenesis of Alzheimer disease - Popugaeva, Elena; Bezprozvanny, Ilya (Frontiers in Molecular Neuroscience, 2013)
Alzheimer disease (AD) is a major threat of XXI century that is responsible for the majority of dementia in the elderly. Development of effective AD-preventing therapies are the top priority tasks for neuroscience research. Amyloid hypothesis of AD is a dominant idea in the field, but so far all amyloid-targeting therapies have failed in clinical trials. In addition to amyloid accumulation, there are consistent reports of abnormal calcium signaling in AD neurons. AD neurons exhibit enhanced intracellular calcium (Ca2+) liberation from the endoplasmic reticulum (ER) and reduced store-operated Ca2+ entry (SOC). These changes occur primarily as a result of ER Ca2+ overload. We argue that normalization of intracellular Ca2+ homeostasis could be a strategy for development of effective disease-modifying therapies. The current review summarizes recent data about changes in ER Ca2+ signaling in AD. Ca2+ channels that are discussed in the current review include: inositol trisphosphate receptors (InsP3R), ryanodine receptors (RyanR), presenilins as ER Ca2+ leak channels and neuronal SOC channels. We discuss how function of these channels is altered in AD and how important are resulting Ca2+ signaling changes for AD pathogenesis.